Fixation of a Proximal Humeral Fracture Using a Novel Intramedullary Cage Construct following a Failed Conservative Treatment - John Macy (Case Reports in Orthopedics)
A majority of proximal humeral fractures are preferably treated conservatively. However, surgical management may be beneficial in proximal humeral fractures with significant displacement or angulation. Unfortunately, the complication rates associated with current surgical procedures for fracture fixation, ORIF and IM devices, can be unacceptably high. A new technology, termed the PH Cage, addresses the technical limitations associated with current technologies available for fixation of proximal humeral fractures. It allows for intramedullary fixation of a PH fracture and provides direct load bearing support to the articular surface and buttresses the medial column during healing. We are presenting our first experience with the PH Cage for the fixation of a PH fracture, which had previously failed conservative management.